Base‐Mediated Defluorosilylation of C(sp2)−F and C(sp3)−F Bonds. Issue 7 (17th January 2019) - Liu, Xiang‐Wei; Zarate, Cayetana; Martin, Ruben
Abstract: The ability to selectively forge C–heteroatom bonds by C−F scission is typically accomplished by metal catalysts, specialized ligands and/or harsh reaction conditions. Described herein is a base‐mediated defluorosilylation of unactivated C(sp 2 )−F and C(sp 3 )−F bonds that obviates the need for metal catalysts. This protocol is characterized by its simplicity, mild reaction conditions, and wide scope, even within the context of late‐stage functionalization, constituting a complementary approach to existing C−Si bond‐forming protocols. Abstract : Base motive : A base‐promoted defluorosilylation of unactivated C(sp 2 )−F and C(sp 3 )−F bonds, obviating the need for transition‐metal catalysis, specialized ligands, or harsh reaction conditions, has been developed. The salient features of this method are the mild reaction conditions, ease of execution, and wide substrate scope, even within the context of late‐stage functionalization of advanced fluorinated building blocks, thus offering a complementary reactivity mode to existing silylation technologies.